A Survey of Clinical Information System Process in General Hospitals of Tehran University of Medical Sciences - H Dargahi; M Ghazi Saeedi; R Safdari; M Hamedan (Tehran University of Medical Sciences, 2010)
Background and Aim: The benefits of a unique computerized medical records and communication equipments is utilized to collect, storage, process, extract and relate to patient care information and management information. If this utilization is in accordance with the needs of managers and staff of medical records, many of the nation's health system problems will be dissolved. Information systems in health supply system by compiling, analyzing and publishing data provide utilization of information improve the health of the society. The purpose of this study is to investigate the process of clinical information systems in general hospitals of Tehran University of Medical Sciences based on available clinical information system in these hospitals. Materials and Methods: This descriptive study is an application study that conducted in order to determine the process of clinical information system in general hospitals of Tehran University of Medical Sciences based on available clinical information in these hospitals. The required data have been collected by a valid and reliable questionnaire. Descriptive statistics were used to analyze data. Results: With regard to the current condition and the importance of survey of the process of clinical information system in the studied hospitals, the authors provided the desired checklist in general hospitals with studying the related system in America, Australia and England countries, on the basis of country requirements in the form of clinical information system processes. We studied clinical information system processes in departments of admission, filling and retrieving, statistical and coding and also soft wares in this department. Discussion and Conclusion: It is necessary to create a coordinated and integrated clinical information system with suitable process and empower experts in the field of proper use of data with regard to the position of information system in each organization and its fundamental role in the adoption of accurate policies. We found that relative frequency of clinical information system processes is more than 60% in this department and clinical information system elements was observed 75% in all the departments except admission.